Integral water security on large tropical basins: a case study for high Andean basins - the Upper Chicamocha River (2023)
ABSTRACT : Water security is a dynamic and complex concept that varies across socio-hydrological contexts. A significant challenge is the lack of governance systems capable of managing complex water competition during water crises. To address this issue, this thesis explores the potential for operationalizing the water security concept for historical analysis and future applications in the Andean highlands through examination of water usage conflicts in the Upper Chicamocha River Basin (UCRB). The thesis provides an Integrated Water Security (IWS) framework, which includes a composite indicator and eight dimensions, to assess the pressures on different aspects of water security and water usage in the UCRB. The study investigates the implications for water security resulting from observed changes over 119 years, using the WEAP model and historical data from 1981-2020, as well as ten composite scenarios for the period 2021-2099 based on historical climate, IPCC-CIMIP5 regional climate models, and research that considers the impact of changes in land use in the Amazon region on water availability. The study validates the local performance of high-resolution precipitation data, CHIRPS v.2 and TerraClimate, and CORDEX CAM-22 driving models from three regional climate models (RCMs) for their potential use in water security assessments. Furthermore, as a complement to the UCRB, the study analyzes the hydrologic transition period from 1956 to 2020 in the Upper Cóncavo River Watershed (UCRW), a glaciated Andean Mountain region of the Sierra Nevada del Cocuy (SNC), which is the largest remaining tropical glacier in Colombia and is part of the same Chicamocha River Basin (CRB). The findings highlight the potential use and challenges of high-resolution datasets in the UCRB and basins with similar topography and hydrometeorology in the Andean region. For the UCRW, the study finds that glacier shrinkage, variable precipitation patterns, and human extraction have significantly altered the UCRW watershed's hydrological capacity to regulate high, low, and mean flows. Communities have become heavily dependent on the surplus baseflow from the shrinking glacier since the 2000s, resulting in unsustainable conditions with potential restrictions on short-term use and major implications for water security in the forthcoming decades. The study's results in the UCRB show that, for the historical period, a general "fair" IWS score was observed 85% of the time, with the remaining 15% classified as "good." Regarding the future period, 60% of the scenarios result in a "fair" IWS score, with 40% classified as "good" but trending towards "fair." However, a historic assessment of the competence in terms of demand coverage for water usage with different priorities suggests that some users were successful (such as mining, thermoelectric, services, environment, aquaculture, and agriculture), while others, such as industry and domestic uses, were the main losers. For the future, the evaluation of competence in terms of demand coverage for water usage with equal and different priorities indicates that mining, thermoelectric, and service-related uses are successful, while other human uses are less successful, with domestic use being the primary loser. The study's findings highlight the significant historical impact of rapid anthropogenic environmental change on water security in the UCRB, with changes in water availability and usage, alterations in temperature and precipitation patterns, climate variability, land use/land cover changes, and population growth presenting challenges to ensuring integrated water security for all users in the region. The future outcomes (2021-2099) highlight the difficulty of ensuring integrated water security for all users and reveal that population dynamics and controlled human interventions will substantially impact the provision of water services. These findings emphasize the necessity of trade-offs to address adverse water security outcomes for all users in a changing climate. Furthermore, the application of the IWS concept in this research provides a framework for analyzing historical or future water security in tropical Andean basins with similar socio-hydrological conditions.